Науково-теоретична підготовка майбутніх учителів до реалізації світоглядного аспекту інтегрованих курсів - Корміна, Лариса; Марценюк, Ірина (My University, 2018)
У статті обґрунтовано доцільність впровадження інтегрованих курсів у навчальний процес загальноосвітньої школи з погляду формування цілісності світоглядних знань учнів. Ефективність реалізації світоглядного аспекту інтегрованих курсів залежить від науково-теоретичної підготовки майбутніх учителів. Визначено, що студентами мають бути усвідомлені основні передумови інтеграції знань у навчанні. Охарактеризовано такі: інтеграція наукових знань – об’єктивно існуючий процес; інтегративні тенденції педагогічної науки і практики; інтегративний характер процесу пізнання; людина як інтегрований об’єкт вивчення; соціально-світоглядні передумови інтегрованих зв’язків у навчанні; філософські основи інтегрованих зв’язків у навчанні; психолого-педагогічні основи інтеграції знань учнів. The article substantiates the expediency of introducing of integrated courses into the educational process of a comprehensive school from the point of view of forming the integrity of outlook knowledge of pupils. The effectiveness of realizing of the outlook aspect of integrated courses depends on the scientific and theoretical training of future teachers. It is determined that students should be aware of the main preconditions for the integration of knowledge in learning process. The following are characterized: integration of scientific knowledge is an objectively existing process; integrative tendencies of pedagogical science and practice; integrative character of the process of cognition; a person as an integrated object of studying process; social and outlook preconditions of integrated relations in education; philosophical foundations of integrated relationships in education; psychological and pedagogical bases of integration of pupils' knowledge.
Keywords: світогляд; світоглядні знання; майбутній учитель; інтеграція знань у навчанні; інтегровані курси; outlook; outlook knowledge; future teacher; integration of knowledge in learning; integrated courses